Human Capital Discovery : The Case Study of Indigenous Vegetable Knowledge as Human Capital of Vicinity Community - Jonjoubsong, Lanthom Jonjoubsong; Phutakool, Pimsiri; Thammabunwarit, Nataporn (Business Administration and Management Journal Review, 2020)
This study has objectives to discover the human capital of a community in vicinity of Bangkok, and to propose a model of human capital discovery of the community through indigenous vegetable (IV) consumption behaviour. The research study on the case of Baan Pandinthong Wat Lumpraong in Nongchong district, Bangkok. Indigenous vegetable survey was taken place around the community, the indigenous vegetable consumption behavious survey was conducted with 121 samples, and semi-structure interview was conducted with 8 representatives of the community. Quantitative data were analysed with descriptive and inference statistic, and social network analysis. Qualitative data were analysed with Google Mymaps and classification technique. The study found that the community had over 60 varieties of IVs. For IV consumption, community members consumed average 24.97 of 30 varieties that were popular growing in the community. The households that came from northeastern region consumed the highest varieties at 28.36 varieties. Meanwhile, the households from eastern, northern, southern and central region consume at 27.67, 25.94, 24.5 and 24.17 varieties, respectively. The data analysis with One-way ANOVA at α = 0.01 shown that the consumption of any regions were non-significant difference. The community members had the average of the IV consumption at 4.10 of 6 or twice a month. The households that came from northeastern region had the highest frequency of consumption at 4.88 of 6. Then, it follows by the households that came from eastern, northern, southern and central region with the consumption rate at 4.72 (four-time per month), 4.26, 4.19 and 3.92 (twice a month) respectively. The data analysis with One-way ANOVA at α = 0.01 shown that the consumption of any regions were significant difference. Most vegetables for consumption of the sample came from purchasing at 58 per cent. The rest of vegetables came from own gardens, neighbour, public area harvesting and from country-side at 23.7, 2.7, 1.3 and 0.4 per cent, respectively. The model of human capital discovery of the community which comprised of five components: IV from both internal and external community, IV consumption, IV knowledge map, opportunities from IV, and IV human capital of the community.